OCEAN VIEW RESORT KEBUMEN WITH AN ECOLOGICAL ARCHITECTURE APPROACH - Iffat Meuthia Arman; Wiwit Setyowati; Didik Nopianto Agung Nugradi; Eko Budi Santoso (Universitas Negeri Semarang, 2025)
Indonesia is the largest archipelago in the world with a variety of natural resources that can be a great tourism potential so that if it can be managed and developed properly, it will provide benefits for the State in the tourism sector. One of the areas that has tourism potential to be visited is Kebumen. Based on the Central Bureau of Statistics in 2023, recorded tourist visits to Kebumen increased by around 2.03 million visits compared to the 2022 period which only reached 1.46 million visits. This was triggered because Kebumen has a variety of tourist attractions, one of which is often visited is the coastal area. With this phenomenon, the need for accommodation such as lodging will also increase and is needed for tourists who are on holiday in Kebumen. Therefore, the planning and design of Ocean View Resort was chosen as one of the lodging and tourist attractions that has a view of the southern sea. The Ocean View Resort planning is located in Ayah District, Kebumen Regency which is one of the locations of the Tourism Area. In its realisation, the facilities in the resort are related to local culture so that the community can contribute. The Ocean View Resort planning is categorised as a four (4) star resort with various complete facilities in it, as well as utilising natural beauty. In addition, the resort applies the concept of Ecological Architecture that utilises the resources around Kebumen. There are five (5) principles of ecological architecture as the basis in designing, namely Solution Grows from Place, Ecological Accounting Informs Design, Design with Nature, Everyone is a Designer, and Make Nature Visible. This concept is applied to minimise the impact of environmental damage and apply building materials from nature so as to give a natural impression and blend with nature.